Fury - Tanenbaum, Robert K. (New York : Pocket Books, 2006)
New York District Attorney Butch Karp and his wife, Marlene, find themselves embroiled in corruption when they set out to bring a group of Brooklyn rapists to justice.
National College of Business and Arts
Keywords: Trials (Rape) -- Fiction; Detective and mystery fiction